¿Por un cine español? - Sánchez González, Santiago (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The abstract is a reflexion about political and social circumstances that have an influence these years in spanish cinema.the coments about the distance of the public ,financiation dificulties etc are thought by the author that understands that there are some aspects in today spanish political landscape that have an influence on the argument of the different films and that leads to the question about which kind of cinema is wanted, if any is wanted,when there are groups of poblation that feel apart from a spanish political and cultural proyect.one can have the feeling that diversity instead of enriching what does is separate